The Role of El Nino Variability and Peatland in Burnt Area and Emitted Carbon in Forest Fire Modeling - Ida Bagus Mandhara Brasika (Forest and Society, 2022)
This study was conducted to model fire occurrence within El Nino variability and peatland distribution. These climate and geographical factors have a significant impact on forest fires in tropical areas such as Indonesia. The re-analysis dataset from ECMWF was observed with respect to climate characteristics in Indonesian El Nino events. The INFERNO (INteractive Fire and Emission algoRithm for Natural envirOnments) was utilized to simulate fires over Borneo Island due to its capability to simulate large-scale fires with simplified parameters. There were some adjustments in this INFERNO model, especially for peat fire as peatland has a significant impact on fires. The first was the contribution of climate to the peat fire which is represented by long-term precipitation. The second was the combustion completeness of peat fire occurrence that is mainly affected by human-induced peat drainage. The result of the model shows that El Nino variability mainly affected peat fires but was unable to well simulate the above-ground fire. It increased the burnt area during strong El Nino but overestimated the fires during low/no El Nino season due to lack of peat fire ignition in the calculation. Moreover, as the model did not provide peat drainage simulation, it underestimated the carbon emission. This model has shown promising results by addressing key features in limited input data, but improving some simulations is necessary for regulating weak/no El Nino conditions and carbon combustion of peat fire.